Kajian Kepentingan Pembinaan Sistem Saliran di Sesebuah Projek Pembinaan Bagi Mengatasi Masalah Banjir - Meor Shamshul Anuar, Marsha Auni; Shareh Musa, Sharifah Meryam; Kasim, Narimah; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
The drainage system was created and built in order to overcome the problem of stagnant water when it rains. Unplanned and poorly maintained, clogged and shallow drainage and drainage systems are the cause of frequent flash floods. The objective of the first study is to identify the type of drainage system used in a construction project. The second objective is to study the problems that occur when the construction of the drainage system in a construction project does not follow the conditions. The third objective of the study is to propose methods for improving the drainage system in a construction project. Next, this study aims to find a good solution to solve the problem of flooding caused by various problems such as drainage systems that are not well maintained and carried out in Selangor. To complete this study, the method used is a qualitative method, namely interviews and observations related to the drainage system in the construction area. Interviews were conducted on respondents involved in this study, namely contractors. The observation method is done to see if the drainage system used is in accordance with the specified conditions. The results of this study show that the surface drainage system is better than other drainage systems. While the problems that often occur due to insufficient drainage systems are caused by the construction materials used as well as clogging problems. The improvements selected were to create silt traps, reservoirs and drainage system cleaning. In conclusion, the researcher hopes that all parties can play their respective roles in keeping the environment clean, especially keeping the drainage system clean so that the flood problem can be reduced.